การปลดจากล้มละลายของบุคคลธรรมดา - สรินยา ลิ่มวณิชสินธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Personal discharge from bankruptcy releases a debtor from certain liabilities, causing the creditors cannot take action against such dischargeable debts. Therefore, main concern for legal measure on the discharge is to balance between the benefits of the honest debtor and the protection of the creditors to receive a fair repayment. Only Section 35 of the Bankruptcy Act (No. 5) B.E. 2542 stipulates criteria for automatic personal discharge, without any other supporting Sections, causing uncertainty and problems to the management of the debtor s estate. The purpose of this study is to examine proper concepts, principles and systems of discharge from bankruptcy under the Thai laws and foreign laws, in order to find proper ways of discharge to reward the honest debtor. The study found that the principle of discharge by court order, and by the effect of the Thai law is appropriate to implementation. However, certain details should be amended or added for better clarification. This thesis suggests following amendment: 1. To clarify the debtor’s acts that shall be deemed dishonesty in the definition of "dishonest persons in bankruptcy" 2. To add causes allowing the receivers to file to suspend counting the period entitling to discharge by specifying various facts depending on serious manners of the debtor.